Increased Within-Network Functional Connectivity May Predict NEDA Status in Fingolimod-Treated MS Patients - Piervincenzi, Claudia; Petsas, Nikolaos; De Giglio, Laura; Carmellini, Maurizio; Giannì, Costanza; Tommasin, Silvia; Pozzilli, Carlo; Pantano, Patrizia (Frontiers in Neurology, 2021)
Only a few studies have evaluated the brain functional changes associated with disease-modifying therapies (DMTs) in multiple sclerosis (MS), though none used a composite measure of clinical and MRI outcomes to evaluate DMT-related brain functional connectivity (FC) measures predictive of short-term outcome. Therefore, we investigated: 1) baseline FC differences between patients who showed evidence of disease activity after a specific DMT and those who did not; 2) DMT-related effects on FC, and; 3) possible relationships between DMT-related FC changes and changes in performance. We used a previously analyzed dataset of 30 relapsing MS patients who underwent fingolimod treatment for 6 months and applied the “no evidence of disease activity” (NEDA-3) status as a clinical response indicator of treatment efficacy. Resting-state fMRI data were analyzed to obtain within- and between-network FC measures. After therapy, NEDA showed significantly reduced within-network FC in the posterior default mode and left frontoparietal networks and increased between-network FC in the posterior default mode/orbitofrontal networks; they also showed PASAT improvement, which was correlated with greater within-network FC decrease in the posterior default mode network and with greater between-network FC increase. No significant longitudinal FC changes were found in the EDA. Taken together, these findings suggest that NEDA status after fingolimod is related to higher within-network FC at baseline and to a consistent functional reorganization after therapy.